Development Learning Media Interactive Powerpoint Integrated Thematic Learning - Silfi Melindawati; Alfiyandri (Jurnal Penelitian Pendidikan IPA, 2023)
This research is motivated by the problem that in the learning process the teacher has used media, but only uses improvised media in the form of books and blackboards as well as media in the form of pictures, thus making students passive during the learning process, this situation is caused by the use of learning media in the learning process only as books and blackboards. Based on these problems the researchers developed interactive powerpoint media in integrated thematic learning. The development model used is the ADDIE model which consists of 5 stages, namely, analysis, design, development, implementation, and evaluation. Based on the results of interactive powerpoint media validation on integrated thematic learning in grade IV elementary schools, it was declared very valid with a validation value range of 3.54, from the results of the practicality test, educators stated that it was very practical with a percentage of 93.37% for learning 1 and learning 2, while the practicality test for students it is stated to be very practical with a percentage of 89.04% for learning 1 and learning 2. So it can be concluded that the development of interactive powerpoint media in integrated thematic learning in grade IV elementary school is very valid and very practical.